Let's Get Fiscal: Extending the Small Macroeconometric Model of the Philippine Economy - Margarita Debuque-Gonzales; John Paul P. Corpus (Philippine Institute for Development Studies (PIDS), 2022)
This study presents a small macroeconometric model with a fiscal sector, extending the model presented in Debuque and Corpus (2022). The model retains the original core blocks of domestic demand, international trade, employment, prices, and monetary sectors, and adds a fiscal sector consisting of equations for government revenues, expenditures, and debt. Behavioral equations are estimated in error-correction form (using ARDL methodology) on quarterly data from 2002 to 2019. In-sample simulations demonstrate acceptable levels of predictive accuracy for most macroeconomic variables, even when producing dynamic forecasts. The model also shows plausible outcomes on the fiscal side in response to shocks in world oil prices, the exchange rate, and primary expenditure, showing the expanded model's policy simulation capabilities. The next steps for developing the model include adding a detailed financial block, modeling the aggregate supply side, and incorporating expectations.
Keywords: 330; macroeconometric model; Philippine economy; forecast; simulation; fiscal sector